Civilizational aspect of global economic development - Z. Z. Adamanova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. At the present stage, globalization processes have not only accelerated, but also acquired a new quality, leading to the fact that economic development is becoming global even at the micro and individual levels. Global economic development has its own patterns and trends that form the agenda for the world community and require a revision of the problem of global governance. Globalization generates new guidelines for economic development at the level of both international and national economies.Goal. The paper aims to study the development of global economy, patterns and trends of globalization processes.Materials and methods. The paper is based on the study of global development trends, processes of differentiation and interaction of fourth-generation civilizations in five main sections. Results and discussion. It was determined that globalization mainly implements the interests of developed countries and civilizations and is a new effective tool for pumping national wealth of less developed countries in their favor, monopolistic appropriation of excess profits, which is the result of the functioning of the global economy, deepening the gap between rich and poor nations.Conclusion. Based on the results of the conducted research, the following trends in the economic dynamics of fourth-generation civilizations can be outlined against the background of deepening globalization. The most typical trends include greater synchronization of economic cycles and crises that have no artificial boundaries. There will be a gradual establishment of the post-industrial economic mode of production with a characteristic set and ratio of devices: public, private and mixed, smallscale, in the service sector, retail trade, partly in agriculture; international in terms of sectors directly involved in the global economy and those that are the property of MNCs. A clearer distinction will be made between the market and non-market sectors – subject to an increase in the share and importance of the latter due to the accelerated development of the socio-cultural sphere, which cannot function entirely on market principles, as well as the development of small-scale subsistence farming for own consumption. One can expect a change in the ratio of the real and virtual economy, which reflects the proportions of reproduction in the curved reality of financial and credit values, which circulate according to their own laws. The powerful flow of financial capital, enhanced by the capabilities of modern information technologies, is expanding the scope of speculative play on stock exchanges.